2019
DOI: 10.1111/ner.12928
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of Urinary Voiding “on Demand” by High-Frequency Stimulation of the S1 Sacral Nerve Root in Anesthetized Rats

Abstract: Objectives: High-frequency (kHz) stimulation of preganglionic pelvic nerve afferents can inhibit voiding in both anesthetized and conscious rats. The afferents travel via the S1 sacral nerve root, which is easier to access than the distal pelvic nerve fibers within the abdominal cavity. We therefore investigated whether voiding could be inhibited by high-frequency stimulation at S1 and how this compared to distal pelvic nerve stimulation.Methods: Urethane-anesthetized rats were instrumented to record bladder p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…HF‐SNM at 1 or 3 kHz was reported to suppress imminent voids for 35–262 sec when SNM was applied for 60 sec after the onset of an imminent void. Bladder pressure continued to rise steeply after the SNM onset and reduced rapidly to a lower level for the remaining 60 sec SNM until a void occurred (17).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…HF‐SNM at 1 or 3 kHz was reported to suppress imminent voids for 35–262 sec when SNM was applied for 60 sec after the onset of an imminent void. Bladder pressure continued to rise steeply after the SNM onset and reduced rapidly to a lower level for the remaining 60 sec SNM until a void occurred (17).…”
Section: Resultsmentioning
confidence: 99%
“…HF-SNM was reported to block or fatigue EUS pressure and allow voiding (14)(15)(16). At the same time, HF-SNM was reported to suppress acute imminent voids (17). All studies reported low bladder pressure when HF-SNM was applied.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…46 Using this approach, stimulation at the sacral root was found to be as effective in suppressing imminent voids as stimulating the distal pelvic nerve bundle. 47 Thus, high-frequency (low kHz range) stimulation may have translational potential for SNS to suppress voids on-demand in some forms of urgency UI. The mode of action of low kHz pelvic nerve stimulation appears to be due to the activation of afferent fibers.…”
Section: Novel Stimulation Paradigmsmentioning
confidence: 99%
“…A more accessible surgical approach could be to access the pelvic nerve afferents as they enter the sacral cord (S1 in Wistar rats) . Using this approach, stimulation at the sacral root was found to be as effective in suppressing imminent voids as stimulating the distal pelvic nerve bundle . Thus, high‐frequency (low kHz range) stimulation may have translational potential for SNS to suppress voids on‐demand in some forms of urgency UI.…”
Section: Can Recent Advances In Understanding the Mechanism Of Action...mentioning
confidence: 99%